Analisis Karakteristik Sensori dan Nutrisi Nutriroot Cookies: Proporsi Tepung Mocaf dan Pisang Raja (Musa Paradisiaca L) dengan Penambahan Tepung Kacang Merah - Khoirunnisa, Aqila; Sutiadiningsih, Any; Sulandari, Lilis; Romadhoni, I. F (Indo-MathEdu Intellectuals Journal, 2025)
The proportion of Mocaf flour with fiber-rich and nutritious raja banana flour provides an innovative alternative in the development of local food products. This study aims to evaluate the sensory test and preferences of NutriRoot Cookies formulated with a combination of mocaf flour, raja banana flour (Musa paradisiaca L), and red bean flour. This study employs an experimental method with various flour proportion treatments, followed by sensory testing of attributes such as color, aroma, texture, taste, shape, and overall preference by trained and semi-trained panelists. The test results showed that the proportions of Mocaf flour and banana flour, as well as the addition of red bean flour, influenced the sensory characteristics of color, aroma, texture, shape, taste, and preference. The best combination was obtained in Formulation F1, which is A100 (70% mocaf flour : 30% banana flour : 35% red bean flour), producing cookies with a sweet and savory taste, crisp texture, even brown color, and better nutritional value. NutriRoot Cookies have the potential to become a healthy snack alternative that supports food security and enhances the value of local agicultural products.